Aprendizagem baseada em problemas no ensino da Tanatologia, no curso de graduação em Enfermagem. - Sampaio, Cynthia Lima; de Sena Neri, Maria Fabiana; Araújo, Michell Ângelo Marques; Caetano, Joselany Áfio; Eloia, Suzana Mara Cordeiro; Souza, Ângela Maria Alves e. (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2018)
Objectives: To report a methodological experience of learning-based on problems in the discipline of Thanatology. Method: Experience report of professors of the baccalaureate degree in nursing using problem situations influenced by the methodology of questioning and problem-based learning. Results: The elaboration of three problem situations broadened the development of the formative process in Thanatology, favored reflections during the program of the discipline and approached the theory of real situations experienced by the students. Conclusions and implications for practice: This methodology was assessed as a viable and low-cost strategy in promoting empowerment on issues of death and dying. In addition, students self-assessed as reflective agents and builders of their own personal and professional growth.